Validation of the Compassion Fatigue Short Scale among Portuguese firefighters - Rodrigues, Fabiana (2023)
Abstract: This study aimed to adapt the Compassion Fatigue-Short Scale to Portugal and examine the reliability and validity of the Portuguese version of the scale (Pt-CF-Short Scale) among Portuguese firefighters. The factor structure of the Pt-CF-Short Scale was compared to the one-factor model fit and a two-factor model and second-order factor model in a sample of 512 firefighters. Confirmatory factor analysis procedures confirmed the good fit of a second-order factor model with two first-order factors (secondary trauma and job burnout). The Pt-CF-Short Scale showed good internal consistency evidence. The Kessler Psychological Distress Scale (K-10), the Brief Symptom Inventory (BSI) and WHOQOOL-Bref were used as convergent measures to assess psychological distress, anxiety, depression, and interpersonal sensitivity and quality of life, respectively. The measure presented a strong correlation with psychological distress and weak and negative association with quality of life. The Pt-CF-Short Scale contributes to understanding compassion fatigue and its correlates within the context of emergency workers. Results indicate that this scale is a valid and reliable assessment tool in evaluating compassion fatigue.